2021
DOI: 10.3390/jcm10245814
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rehospitalization and Mortality in Diabetes-Related Hospital Admissions

Abstract: The risk factors of rehospitalization and death post-discharge in diabetes-related hospital admissions are not fully understood. To determine them, a population-based retrospective epidemiological survey was performed on diabetes-related admissions from the Polish national database. Logistic regression models were used, in which the dependent variables were rehospitalization due to diabetes complications and death within 90 days after the index hospitalization. In 2017, there were 74,248 hospitalizations relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A similar phenomenon was observed among those hospitalized due to type 2 diabetes: between 2010 and 2018, the in-hospital mortality rate increased from 1.9% to 2.76% among male patients and from 2.37% to 3.37% among female patients [ 24 ]. Moreover, Kozioł et al showed that of 74 248 diabetes-related hospitalizations in 2017, 7.3% resulted in death within 90 days following discharge [ 26 ]. Findings from this study showed differences in in-hospital mortality rates in type 1 (2.1%) and type 2 (3.3%) diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar phenomenon was observed among those hospitalized due to type 2 diabetes: between 2010 and 2018, the in-hospital mortality rate increased from 1.9% to 2.76% among male patients and from 2.37% to 3.37% among female patients [ 24 ]. Moreover, Kozioł et al showed that of 74 248 diabetes-related hospitalizations in 2017, 7.3% resulted in death within 90 days following discharge [ 26 ]. Findings from this study showed differences in in-hospital mortality rates in type 1 (2.1%) and type 2 (3.3%) diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These data can be helpful for clinicians and policymakers to improve the management of diabetes in Poland. However, a limited amount of research on diabetes is based on national registries [ 22 26 ]. Most of the previously published data are focused on epidemiological analyses aimed at the prevalence of diabetes [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a chronic disease with chronic complications, diabetes sufferers are often faced with the challenge of short-term and long-term complications associated with frequent readmissions increasing length of hospital stays, and death. 9 One way to prevent frequent re-admission and early development of complications is to ensure that individuals with diabetes have adequate knowledge and ability for self-management. Self-management refers to a set of skilled behaviors engaged in managing one’s illness.…”
Section: Introductionmentioning
confidence: 99%